Variation of cross country ski characteristics - Breitschädel, F. (Book of Abstracts. 5th International Congress on Science and Skiing, Dec. 14 - 19, 2010, St. Christoph am Arlberg, 2010)
INTRODUCTION: In cross-country skiing the technical equipment of an athlete constitutes a substantial part to the end performance. Ekström (1981) for instance reported a major effect of the ski span characteristics on the gliding results already 29 years ago. Each year world class athletes spend a large amount of time together with their ski technicians to find the best possible skis. The interest of this study is to find out if different Norwegian national teams select skating skis with similar characteristics.